Psychological adaptation in international students’ migration: Social support, meaning in life, and resilience in China - Mahmood, Rabia; Wang, Freda Yangrong; Ahmed, Waqas; Mahmood, Sadaf; Suleman, Rao Muhammad Faisal; Mahood, Unsa (Journal of International Students, 2026)
As international student mobility increases, psychological adaptation has become a central concern, particularly in contexts where cultural unfamiliarity intersects with academic pressure. This study investigates how social support shapes the psychological well-being of international students in China, examining both direct effects and indirect pathways through meaning in life and resilience. Drawing on debates on migrant integration and the stress-buffering framework, a cross-sectional survey was conducted with 503 international students from 61 countries. Partial least squares structural equation modeling (PLS-SEM) was employed to test the proposed relationships. The findings indicate that social support significantly predicts resilience and meaning in life, which, in turn, enhance psychological well-being. Mediation analyses confirm significant indirect effects, and the model demonstrates strong explanatory power. These results position psychological well-being as a core dimension of migrant integration rather than a secondary outcome.